Strategic Approach Model for Investigating the Cause of Maritime Accidents - ÖZDEMİR, Ünal; GÜNEROĞLU, Abdulaziz (Promet - Traffic&Transportation, 2015)
It is commonly accepted that the majority of maritime causalities are caused by human factors/errors. The role of human factor in maritime accident and the possible reasons of this argument can be quantitatively evaluated based on expert knowledge and multiple criteria decision-making (MCDM) methodology. To investigate what makes the first “human factor” in ship accidents, a hybrid approach was applied in this study. Two methods, the decision-making trial and evaluation laboratory (DEMATEL) and the analytical network process (ANP) were proposed to evaluate the importance level of the human factors in maritime casualties. Quantitative evaluations of the human errors in maritime operations can greatly improve the decision-making process and reduce potential risks. As a result of this study, the top three priorities in the evaluation systems were found as: ‘ability, skills, knowledge’ (8.94%), ‘physical condition’ (8.77%), ‘weather - sea conditions’ (8.21%) and the least important criterion was ‘cargo characteristics’ (2.21%).